EFFECT OF Cr(VI) IONS ON THE EFFECTIVENESS OF CHLOROPHENOL PHOTODEGRADATION - Endang Tri Wahyuni; Ngatidjo Hadipranoto; Iqmal Tahir; Bambang Haryo Gatut Tamtama (Universitas Gadjah Mada, 2004)
In order to solve environmental problems due to chlorophenol compound and which is hazardous and carcinogenic, the effect of Cr(VI) ions on the chlorophenol photodegradation effectiveness has been evaluated. Photodegradation process was carried out in a closed reactor by batch sistem, by exposing the UV lamp into a solution containing chlorophenol and Cr(VI) ions for a period of time. Then the solution was analyzed by gas chromatography for determination of the residual chlorophenol concentration. In this research, the influences of reaction time, Cr(VI) ions concentration, and solution pH on the photodegradation results were also evaluated. The research results indicated that the effectiveness of the photodegradation increases when ion Cr(VI) was added. The improvement of the effectiveness is proportional with the increase of the concentration of Cr(VI) added. The effectiveness of the photodegradation is also influenced by solution pH, and the highest is reached at pH < 2. Chlorophenol photodegradation follows first order reaction. The respective rate reaction constants for chlorophenol photodegradation in the absence and in the presence of Cr(VI) ions are 4.91x 10-2 and 11.41x 10-2 hours-1